Sistema de control eléctrico remoto en la galería histórica de la Carrera de Computación de la ESPAM-MFL - Gómez Coaboy, Edy Lorenz (2018)
The present work had as main porpoise the automation of the electrical system in the historical gallery of Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, in the Computation Career. It began with the dialogue with the Career director to determine the necessary requirements to start the development of the system, later the area of location of the historic gallery to undertake the systematization of electric control was determined. In order to continue with the development and modeling of the device that would allow remote electrical control, it was necessary to construct a prototype with most of its electronically based components. With regard to control of the luminaires, a web application with an Arduino compatible IDE was created, which allows manipulation from anywhere in the world with access to the internet. At the beginning of the tests until obtaining favorable results, it was determined that when working for objectives throughout the design and implementation process is a favorable option, at the time of the execution of a project. With the implementation of the system, was allowed to take efficient management of automation of luminaires.